1983
DOI: 10.1007/bf00397195
|View full text |Cite
|
Sign up to set email alerts
|

Long-duration, high-frequency plant regeneration from cereal tissue cultures

Abstract: By visual examination of calli derived from germinating seeds of wheat, oats, rice, proso millet, and pearl millet it has been possible to visually select embryogenic (E) callus which, on transfer to a regeneration medium, forms plants an average of 33 times more frequently than non-embryogenic (NE) callus of equal mass. Embryogenic callus consists of small isodiametric cells averaging 31 μm in diameter; NE callus consists of long tubular cells averaging 52 μm in width and 355 μm in length. Production of E cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(55 citation statements)
references
References 10 publications
3
51
0
Order By: Relevance
“…These studies have shown that callus that gives rise to somatic embryos is usually compact and nodular and that this embryogenic callus can be microscopically distinguished from non-embryogenic callus (Vasil 1985;Nabors et al 1983). MS medium has been used successfully to induce embryogenic callus cultures from a large number of gramineous species (Nabors et al 1983;Vasil 1985;Ahloowalia 1990). In the present study this common MS medium proved successful for the induction of embryogenic callus cultures from three Allium species using zygotic embryos as the explant material.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have shown that callus that gives rise to somatic embryos is usually compact and nodular and that this embryogenic callus can be microscopically distinguished from non-embryogenic callus (Vasil 1985;Nabors et al 1983). MS medium has been used successfully to induce embryogenic callus cultures from a large number of gramineous species (Nabors et al 1983;Vasil 1985;Ahloowalia 1990). In the present study this common MS medium proved successful for the induction of embryogenic callus cultures from three Allium species using zygotic embryos as the explant material.…”
Section: Discussionmentioning
confidence: 99%
“…According to our observation, the calli arising from the edges of explants obtained in this work were typically non friable, whitish and/or hard. No green points were observed on the surface of any of these calli, which would have led to the possible conclusion that the calli were organogenic (Nabors et al, 1983). We hypothesized that these calli did not participate in the organogenic process and therefore did not give rise to the emerging shoot.…”
Section: Acquisition Of Organogenic Competencementioning
confidence: 99%
“…The culture environment used was Murashige-Skoog, 1962, (Table 1) In general, the possibility of applying such methods depends on the species, the donor material, age of the explants or the environment's formula (Lührs & Lörz, 1987;Nabors et al, 1983;Popelka & Altpeter, 2001;Maës et al, 1996;Dahleen, 1999), (Lührs & Lörz, 1987;Barro et al, 1999, Thomas & Scott, 1985Maës et al, 1996, as cited in Gana, 2010.…”
Section: Methodsmentioning
confidence: 99%
“…If it's not cultivated on time, the callus grows old and changes it's colour pursuant to metabolite accumulation. According to Nabors, 1983 the callus can be a recuperative type when it leads to complete plant formation or a non-recuperative type when it grows abundantly and it regenerates either roots, either buds, but never complete plants.…”
Section: Introductionmentioning
confidence: 99%